Synthesis 5-hydroxymethylfurfural (5-HMF) from fructose over cetyl trimethylammonium bromide-directed mesoporous alumina catalyst: effect of cetyl trimethylammonium bromide amount and calcination temperature - Hoşgün, Halit Levent; Türe, Ayşe Gül; Hosgun, E. Zafer; Bozan, Berrin (Springer, 2020)
In this study, mesoporous alumina was synthesized using aluminium isopropoxide as Al precursor and cationic surfactant cetyl trimethylammonium bromide (CTAB) as structure directing agent and it was tested in the dehydration reaction of fructose into 5-HMF. The experiments were carried out in a microwave reactor at 200 degrees C for 5 min. The various ratio of CTAB/Al2O3 and calcination temperature between 400 and 700 degrees C were selected as synthesis parameters. The synthesized samples were analyzed by BET and XRD. The highest surface area was obtained as 602.22 m(2)/g with the weight ratio of CTAB to Al2O3 of 1.00 at the calcination temperature of 400 degrees C. When calcination temperature increased from 400 to 700 degrees C, surface area decreased into 286.14 m(2)/g. N-2 adsorption/desorption isotherms of samples showed characteristic mesoporous type IV according to IUPAC classification. According to XRD patterns, all catalysts were in the amorphous structure. The maximum 5-HMF yield of 51% was achieved with the alumina catalyst calcined at 400 degrees C and CTAB/Al2O3 ratio of 1.0. Although the surface area decreased by rising the calcination temperature from 400 to 550 degrees C, the fructose conversion reached the highest value (97.54%).
Keywords: Alumina; Sol-gel synthesis; CTAB; Fructose; 5-HMF